Conférence: «Science politique et féminisme - Rencontre entre deux champs» - Institut de recherches et d'études féministes; Réseau Québécois en études féministes (2018)
Avec Geneviève Pagé, membre de l'Institut de recherches et d'études féministes et professeure au Département de science politique.
Keywords: approches et analyses; discipline; genre; histoire du féminisme; identités LGBTQIA2+; inégalités; militance; rapports sociaux de sexe; science politique; sexisme; sexualité; systèmes d'oppression; thématiques

Inconsequence: Lesbian representation and the logic of sexual sequence - Jagose, Annamarie (Cornell University Press, 2018)
The field of lesbian studies is often framed in terms of the relation between lesbianism and invisibility. Annamarie Jagose here takes a radical new approach, suggesting that the focus on invisibility and visibility is perhaps not the most productive way of looking at lesbian representability. Jagose argues that the theoretical preoccupation with metaphors of visibility is part of the problem it attempts to remedy. In her account, the regulatory difference between heterosexuality and homosexuality relies less on codes of visual recognition than on a cultural adherence to the force of first order, second order sexual sequence. As Jagose points out, sequence does not simply specify what comes before and what comes after; it also implies precedence: what comes first and what comes second. Jagose reads canonical novels by Charles Dickens, Henry James, Virginia Woolf, and Daphne du Maurier, drawing upon their elaboration of sexual sequence. In these innovative readings, tropes such as first and second, origin and outcome, and heterosexuality and homosexuality are shown to reinforce heterosexual precedence. Inconsequence intervenes in current debates in lesbian historiography, taking as its pivotal moment the fin-de-siècle phenomenon of the sexological codification of sexual taxonomies and concluding with a reading of a post-Kinsey pulp sexological text. Throughout, Jagose reminds us that categories of sexual registration are always back-formations, secondary, and belated, not only for those who identify as lesbian but also for all sexual subjects.
Keywords: approches et analyses; arts; discipline; discours dominant; littérature; personnes lesbiennes; ressource en ligne; sexualité; systèmes d'oppression; thématiques; études littéraires

My butch career: A memoir - Newton, Esther (Duke University Press, 2018)
During her difficult childhood, Esther Newton recalls that she “became an anti-girl, a girl refusenik, caught between genders,” and that her “child body was a strong and capable instrument stuffed into the word ‘girl.’” Later, in early adulthood, as she was on her way to becoming a trailblazing figure in gay and lesbian studies, she “had already chosen higher education over the strongest passion in my life, my love for women, because the two seemed incompatible.” In My Butch Career Newton tells the compelling, disarming, and at times sexy story of her struggle to write, teach, and find love, all while coming to terms with her identity during a particularly intense time of homophobic persecution in the twentieth century. Newton recounts a series of traumas and conflicts, from being molested as a child to her failed attempts to live a “normal,” straight life in high school and college. She discusses being denied tenure at Queens College—despite having written the foundational Mother Camp—and nearly again so at SUNY Purchase. With humor and grace, she describes the influence her father Saul's strong masculinity had on her, her introduction to middle-class gay life, and her love affairs—including one with a well-known abstract painter and another with a French academic she met on a spur-of-the-moment trip to Mexico and with whom she traveled throughout France and Switzerland. By age forty, where Newton's narrative ends, she began to achieve personal and scholarly stability in the company of the first politicized generation of out lesbian and gay scholars with whom she helped create gender and sexuality studies. Affecting and immediate, My Butch Career is a story of a gender outlaw in the making, an invaluable account of a beloved and influential figure in LGBT history, and a powerful reminder of just how recently it has been possible to be an openly queer academic.
Keywords: amériques; approches et analyses; autobiographie; butch; histoire et politique; hétérosexisme; identités LGBTQIA2+; queer; ressource en ligne; régions géographiques; sexualité; systèmes d'oppression; thématiques; travail; violences; états-unis